Application of Natural Zeolite in Methylene Blue Wastewater Treatment Process by Adsorption Method - Amelia, Shinta; Maryudi, Maryudi (Jurnal Bahan Alam Terbarukan, 2019)
Textile industry waste contains dyes that are difficult to decompose naturally and cause disruption of ecosystems in water. The colorant that is often used in the textile industry is methylene blue which is a cationic heterocyclic aromatic compound. This compound is so stable that it is difficult to decompose naturally and is harmful to the environment in large concentrations. Therefore, we need a waste treatment technology that can reduce the concentration of dye waste in water. So far, the adsorption method remains the most efficient and effective technique in removing dyes because of its relatively large adsorption capacity. One method that can be used is the adsorption method using natural zeolite. Zeolite is one of the non-metal mineral commodities or multipurpose industrial minerals, one of which is as an adsorbent or adsorbent media. This study aims to determine the potential of natural zeolite in absorbing methylene blue with variations in the concentration of methylene blue and various sizes of natural zeolite mesh. The procedures in this experiment include, the preparation of natural zeolite with size variations of 20-60 mesh, 60-100 mesh and> 100 mesh and variations in the concentration of methylene blue used 15 ppm, 30 ppm and 45 ppm with contact time from 0 to 180 minutes. From the results of the study it was found that the smaller the size of natural zeolite used, the greater the percentage of dye removal that is at mesh size> 100 mesh the percentage of dye removal was 32.11%. As for the variation of the concentration of methylene blue, the smaller the concentration, the natural zeolite can work optimally ie at a concentration of 15 ppm at 180 minutes the remaining methylene blue concentration of 0.145 ppm.